Prime time violence [videorecording] - Harris, Bob; Kurtis, Bill; Stoner, Barry (Kurtis Productions & A%E Networks, 1994)
The ever-growing incidence of violence on television is examined. Includes debates of producers, politicians and parents over television violence. It takes a look at U.S. government censorship and the future of TV violence.